"A Sword of Wrath, the Executor of Sinister Adventures" Domestic Islamophobia and International Black Muslim Solidarities during the Cold War - Caldwell, Will (2019)
FBI repression of "Black Muslim" groups such as the Moorish Science Temple of America and the Nation of Islam emerged from institutionalized forms of Islamophobia preceding the War on Terror. This article examines the broader Cold War policies that criminalized Black conversion to Islam as a treasonous affiliation with "un-American" forces.